2017
DOI: 10.15376/biores.12.3.4830-4853
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production from Steam Reforming of Acetic Acid over Ni-Fe/Palygorskite Modified with Cerium

Abstract: The steam reforming of acetic acid (SRA) was carried out in a fixed-bed tubular reactor with Ni-Fe/ceria-palygorskite (CPG) catalysts. The asprepared catalysts were analyzed by N2 adsorption-desorption, scanning electron microscopy coupled with energy dispersive spectroscopy (SEM-EDS), H2 temperature programmed reduction (H2-TPR), and X-ray diffraction (XRD). The results of H2-TPR and XRD showed that the addition of CeO2 increased the hydrogen consumption of catalysts and the interaction force between active c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…It was also reported that, for several Ni-based catalysts, La 2 O 3 led to a decrease in coke formation [194,206,207,217,233,234] and KOH and MgO improved the stability [194,206,207,[234][235][236]. It was also observed in several studies using Ni-based catalysts that the addition of CeO 2 improved the catalyst stability, namely through the decrease of coke production [195,197,[215][216][217][218]. So, the addition of basic oxides to the Al 2 O 3 support, in a general way, enhanced the catalytic performance.…”
Section: Deactivationmentioning
confidence: 80%
See 3 more Smart Citations
“…It was also reported that, for several Ni-based catalysts, La 2 O 3 led to a decrease in coke formation [194,206,207,217,233,234] and KOH and MgO improved the stability [194,206,207,[234][235][236]. It was also observed in several studies using Ni-based catalysts that the addition of CeO 2 improved the catalyst stability, namely through the decrease of coke production [195,197,[215][216][217][218]. So, the addition of basic oxides to the Al 2 O 3 support, in a general way, enhanced the catalytic performance.…”
Section: Deactivationmentioning
confidence: 80%
“…In the work of Savuto et al [197] (who studied the steam refo compounds), mayenite (Ca12Al14O33) was used as support of Ni, show tion properties that increase the resistance of the catalyst towards coke other hand, Choi et al [209] verified that a Ni/Al2O3 catalyst with a lar basic sites and few middle and strong basic sites is required to impro formance and minimize coke formation (in acetic acid steam reformin It was also reported that, for several Ni-based catalysts, La2O3 l coke formation [194,206,207,217,233,234] and KOH and MgO imp [194,206,207,[234][235][236]. It was also observed in several studies using Nithe addition of CeO2 improved the catalyst stability, namely through t production [195,197,[215][216][217][218]. So, the addition of basic oxides to the In the work of Savuto et al [197] (who studied the steam reforming of tar model compounds), mayenite (Ca 12 Al 14 O 33 ) was used as support of Ni, showing excellent oxidation properties that increase the resistance of the catalyst towards coke deposition.…”
Section: Deactivationmentioning
confidence: 83%
See 2 more Smart Citations
“…It was reported that Cr inhibited the formation of Ni 3 C and can modify the metal sites forming alloys with Ni [132,133], La 2 O 3 led to a decrease in coke formation [105,[132][133][134][135][136], K and MgO improved the stability [105,117,132,133,[136][137][138][139], and TiO 2 decreased the conversion [132]. It was also observed that the addition of CeO 2 improved the activity and stability of the catalyst [106,108,114,135,[140][141][142].…”
Section: Effect Of Promotersmentioning
confidence: 96%